2007
DOI: 10.1002/jmv.21010
|View full text |Cite
|
Sign up to set email alerts
|

Use of replacement blood donors to study the epidemiology of major blood‐borne viruses in the general population of Maputo, Mozambique

Abstract: The seroprevalence rates of human immunodeficiency virus (HIV), human T-cell leukemia/lymphoma virus (HTLV), hepatitis B virus (HBV), hepatitis D virus (HDV), and hepatitis C virus (HCV) in Mozambique are poorly documented. The epidemiology of these infections was studied in the Maputo region. All donors attending the blood bank during the study period were interviewed and underwent serological and molecular tests for markers of virus exposure. Thus, 1,578 consecutive replacement blood donors were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
75
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 38 publications
11
75
1
1
Order By: Relevance
“…In a recent survey in Central, Western, and Eastern Franco-phone African regions, all 7 countries surveyed reported less than 30% females in their donor population [17]. Reports from Anglophone East and Southern African countries have also shown a male dominance in their blood donation programs [18]. Our finding is in agreement with previous report among blood donors in India which indicated that female gender is less disposed to blood donation [19].…”
Section: Discussionsupporting
confidence: 90%
“…In a recent survey in Central, Western, and Eastern Franco-phone African regions, all 7 countries surveyed reported less than 30% females in their donor population [17]. Reports from Anglophone East and Southern African countries have also shown a male dominance in their blood donation programs [18]. Our finding is in agreement with previous report among blood donors in India which indicated that female gender is less disposed to blood donation [19].…”
Section: Discussionsupporting
confidence: 90%
“…In a Senegalese blood transfusion center, the seroprevalence was 0.56%, 17 in Guinea 0.84%, 18 in Nigeria 2.7%, 19 in Tanzania 3.8%, 20 in Burkina Faso 4.6%, 21 and 13% in Mozambique. 22 This study showed an HBV prevalence of 14.9% among our study population. Another recent study conducted at the CNTS has revealed an HBV prevalence of 15.25%.…”
Section: Discussionmentioning
confidence: 47%
“…Lower prevalence of coinfection has been recorded in Cameroon (0.69%), 25 Nigeria (0.4%), 19 and the Democratic Republic of the Congo (1%). 22,24 However, higher coinfection seroprevalence were recorded in Mozambique (2%), 22 Congo Brazzaville (5.76%), 26 and Ethiopia (34.0%). 27 Our results showed that HIV-seropositive patients were more likely to be infected by HBsAg than HIV seronegative patients (OR ¼ 2.02; CI: 1.63-2.49).This result is similar to studies done in Mozambique 22 and Zimbabwe.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations